Research and field testing of cabled intelligent stratified oil production technology - DENG Jibin, KANG Yuyang, YAN Weijie, YE Hong, ZHANG Xiangyang (Youqicang pingjia yu kaifa)
The complex small fault block oilfields in Jiangsu are mainly developed through waterflooding with stratified injection. Currently, intelligent stratified injection is applied to improve injection-production coordination and enhance recovery efficiency. Due to the low level of stratified control in production wells and the unclear understanding of the relationship and degree of effectiveness of stratified water injection, issues such as interlayer interference in production wells, single-layer water breakthrough, and rapid water cut increases are prominent. To achieve injection-production coordination, alleviate interlayer and areal contradictions during the high water cut period, reduce ineffective water cycling, and control the rise in water cut of production wells, a cabled intelligent stratified oil production technology was developed. Flow rate, water cut, pressure, and temperature sensors suitable for the high-temperature, high-pressure, corrosive, and scaling-prone downhole environment were selected. Reliable stratified flow control devices and control technologies were adopted, and the spatial layout of components and overall mechanical structure of the stratified production allocator were optimally designed. Different bidirectional transmission cables and connection technologies were selected, the control circuits of the production allocator and a ground-integrated control system were developed, and the supporting downhole stratified oil production strings were optimized. Tool and implementation costs were reduced, enabling real-time continuous monitoring of downhole stratified production parameters and wireless remote control of the stratified production allocator. Field tests, including alternating single-layer production, stratified production allocation, and coupled adjustment, were conducted. The tests confirmed the conclusions of pre-test reservoir dynamic analysis and verified the performance of the intelligent stratified oil production tools and strings. Injection-production coupling, enhanced oil production, water cut control, and stratified measurement and adjustment were achieved, with the water cut of the test well reduced by 38.8%. The application of this technology can provide a basis for fine geological analysis and potential exploration of oil reservoirs, significantly enhancing the intelligent level of oilfield production.